Profil Pengguna Tinder Berusia Dewasa Awal - Adib Fakhri Najib Ahda; Fanni Putri Diantina (Bandung Conference Series: Psychology Science, 2023)
Abstract. One of the conveniences of internet-based technology is suggestions for finding partners, with the emergence of various online dating applications. One of the most used online dating applications in the world is Tinder, including in Indonesia. Tinder makes it easy to find suitable dates for its users. Each User has different motives and excessive use has the potential to cause annoyance to problematic Tinder users. This study aims to find out how strong the relationship is between Tinder use motive and personality type according to the big five theory dimensions for problematic Tinder users. This study used a quantitative approach with the Spearman correlation test technique which was conducted on 381 respondents with an age range of 18 to 25 years. The measurement instruments used were the Tinder Use Motive Scale (TUMS) developed by Orosz et al (2018), the Big Five Inventory (BFI) developed by Pervin & John (1991), the Problematic Tinder Use Scale (PTUS) developed by Orosz et al ( 2016).. The results of the study show that there is a relationship between Tinder use motives and personality types according to the dimensions of the big five theory on problematic Tinder users. Agreeableness has the strongest relationship with self-esteem enhancement with a value of r=0.113, conscientiousness with boredom with a value of r=-0.103, neuroticism with sex with a value of r=0.104, openness to experience and extraversion are related to boredom with a value of r=-0.093 and r =0.115 Abstrak.Salah satu kemudahan pada teknologi berbasis internet adalah saran pencarian pasangan, dengan munculnya berbagai aplikasi kencan online. Salah satu aplikasi kencan online yang paling banyak digunakan di dunia adalah Tinder, termasuk di Indonesia. Tinder memberikan kemudahan untuk menemukan pasangan kencan yang cocok untuk penggunanya. Setiap Penggunanya memiliki motif yang berbeda dan penggunaan berlebihan berpotensi menimbulkan gangguan pengguna Tinder yang bermasalah. Penelitian ini bertujuan untuk mengetahui seberapa kuat hubungan antara Tinder use motive dengan tipe kepribadian menurut dimensi big five theory pada pengguna Tinder yang bermasalah. Penelitian ini menggunakan pendekatan kuantitatif dengan teknik uji korelasi spearman yang dilakukan kepada 381 responden dengan rentang usia 18 hingga 25 tahun. Instrumen pengukuran yang digunakan adalah Tinder Use Motive Scale (TUMS) yang dikembangkan oleh Orosz dkk (2018),Big Five Inventory (BFI) yang dikembangkan oleh Pervin & John (1991), Problematic Tinder Use Scale (PTUS) yang dikembangkan oleh Orosz dkk (2016).. Hasil penelitian menunjukan bahwa ada hubungan antara Tinder use motive dengan tipe kepribadian menurut dimensi big five theory pada problematic Tinder user. Agreeableness memiliki hubungan paling kuat dengan self esteem enhancement dengan nilai r=0.113, conscientiousness dengan boredom dengan nilai r=-0.103, neuroticism dengan sex dengan nilai r=0.104, openness to experience dan extraversion berhubungan dengan boredom dengan nilai r=-0.093 dan r=0.115